2010
DOI: 10.1063/1.3280388
|View full text |Cite
|
Sign up to set email alerts
|

The influence of a single thiol group on the electronic and optical properties of the smallest diamondoid adamantane

Abstract: At the nanoscale, the surface becomes pivotal for the properties of semiconductors due to an increased surface-to-bulk ratio. Surface functionalization is a means to include semiconductor nanocrystals into devices. In this comprehensive experimental study we determine in detail the effect of a single thiol functional group on the electronic and optical properties of the hydrogen-passivated nanodiamond adamantane. We find that the optical properties of the diamondoid are strongly affected due to a drastic chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 51 publications
2
41
0
Order By: Relevance
“…6 we present the energies of the first purely diamondoid -S-type state together with the energies of n-‫ء‬ SH states as a function of diamondoid size. 40 By increasing the size of the diamondoid subunit, the purely diamondoid -S transition shifts to lower energies in thiol functionalized diamondoids ͑Fig. 40 Species in which S-type states lie energetically below these states, however, are good candidates for exhibiting fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…6 we present the energies of the first purely diamondoid -S-type state together with the energies of n-‫ء‬ SH states as a function of diamondoid size. 40 By increasing the size of the diamondoid subunit, the purely diamondoid -S transition shifts to lower energies in thiol functionalized diamondoids ͑Fig. 40 Species in which S-type states lie energetically below these states, however, are good candidates for exhibiting fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…The growing interest to diamondoids is determined by their potential for nanoelectronics140–143 and their oxidation is considered among the most promising preparative functionalization approaches 144–147. The HOMOs of diamondoids are typically highly delocalized and their radical cations display pronounced spin/charge delocalizations over the entire cage.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…More specifically, the lowest unoccupied molecular orbital (LUMO) of C 60 lines up closer to the Fermi level of the metallic substrates than does its highest occupied molecular orbital (HOMO). Seminal optical absorption measurements20 revealed that the opposite holds for diamantane. This suggests that diamantane–C 60 (Dia–C 60 ) hybrid molecules should be ideal molecular rectifiers by combining a negative electron affinity moiety (localized on diamantane) with a positive electron affinity segment (localized on C 60 ).…”
Section: Resultsmentioning
confidence: 99%